Serum proteomic and metabolomic profiling of hepatocellular carcinoma patients co-infected with Clonorchis sinensis - Tang, Zeli; Wei, Caibiao; Deng, Xueling; Lin, Qiumei; Hu, Qiping; Li, Shitao; Wang, Jilong; Wu, Yuhong; Liu, Dengyu; Fang, Min; Zhan, Tingzheng (Frontiers in Immunology, 2025)
BackgroundClonorchis sinensis (C. sinensis) infection is a significant risk factor for hepatocellular carcinoma (HCC), yet its underlying mechanisms remain poorly understood. This study aimed to investigate the impact of C. sinensis infection on the serum proteomic and metabolomic profiling of HCC patients, focusing on the potential mechanisms.MethodA retrospective clinical analysis was conducted on 1121 HCC patients, comparing those with and without C. sinensis infection. The influence of C. sinensis on serum proteome and metabolome in HCC was further assessed.ResultC. sinensis infection correlated with a younger age at cancer onset, male predominance, advanced cancer stage, liver cirrhosis, and microvascular invasion in HCC patients. It also associated with shorter overall survival (OS) and recurrence-free survival (RFS). The levels of blood lipids (e.g., APO-A, HDL-C, and TG) were significantly altered after C. sinensis infection. Proteomic and metabolomic analyses revealed metabolic reprogramming caused by C. sinensis, with excessive depletion of argininosuccinate synthase (ASS) and D-glucose as potential factors in C. sinensis-associated HCC malignancy. Key molecules ILF2, CNN2, OLFM4, NOTCH3, and LysoPA were implicated in HCC progression. Furthermore, C. sinensis triggered inflammation, insulin resistance, and pro-tumor immune escape, and exacerbated the complication of degenerative diseases.ConclusionThis study not only provides compelling evidence for elucidating the mechanisms underlying C. sinensis-mediated HCC development but also identifies potential therapeutic targets for HCC patients co-infected with C. sinensis.